Phosphorylation of Thr-178 and Thr-184 in the TAK1 T-loop Is Required for Interleukin (IL)-1-mediated Optimal NFκB and AP-1 Activation as Well as IL-6 Gene Expression - Yu, Yang (American Society for Biochemistry and Molecular Biology, 2008)
TAK1 (transforming growth factor-β-activated kinase 1), a mitogen-activated protein kinase kinase kinase, is activated by various cytokines, including interleukin-1 (IL-1). However, the precise regulation for TAK1 activation at the molecular level is still not fully understood. Here we report that dual phosphorylation of Thr-178 and Thr-184 residues within the kinase activation loop of TAK1 is essential for TAK1-mediated NFκB and AP-1 activation. Once co-overexpressed with TAB1, TAK1 mutant with alanine substitution of these two residues fails to activate IKKβ-mediated NFκB and JNK-mediated AP-1, whereas TAK1 mutant with replacement of these two sites with acidic residues acts like the TAK1 wild type. Consistently, TAK1 mutant with alanine substitution of these two residues severely inhibits IL-1-induced NFκB and AP-1 activities, whereas TAK1 mutant with replacement of these two sites with acidic residues slightly enhances IL-1-induced NFκB and AP-1 activities compared with the TAK1 wild-type. IL-1 induces the phosphorylation of endogenous TAK1 at Thr-178 and Thr-184. Reconstitution of TAK1-deficient mouse embryo fibroblast cells with wild-type TAK1 or a TAK1 mutant containing threonine 178 and 184 to alanine mutations revealed the importance of these two sites in IL-1-mediated IKK-NFκB and JNK-AP-1 activation as well as IL-1-induced IL-6 gene expression. Our finding is the first report that substitution of key serine/threonine residues with acidic residues mimics the phosphorylated state of TAK1 and renders TAK1 active during its induced activation.